1990
DOI: 10.1029/jd095id10p16865
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of soil and canopy exchange rates in the Amazon rain forest using 222Rn

Abstract: Measurements of the emission of 222Rn from Amazon forest soils, and profiles of 222Rn in air were used to study the ventilation of the soil atmosphere and the nocturnal forest canopy. The emission of 222Rn from the yellow clay soils dominant in the study area averaged 0.38±0.07 atom cm−2 s−1. Nearby sand soils had similar fluxes, averaging 0.30 ± 0.07 atom cm−2 s−1. The effective diffusivity in the clay soil (0.008±0.004 cm2 s−1), was lower than that for the sand soil (0.033±0.030 cm2 s−1). Profiles of 222Rn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 18 publications
7
42
1
3
Order By: Relevance
“…From the results of the 222 Rn method, average diffusion coefficients and relaxation depths of CO 2 and CH 4 were similar to previous values in aerated sandy soils (Dörr and Münnich 1990;Trumbore, 1990;Dueñas et al 1999;Kim and Tanaka 2002). There are yet few reports for a diffusion coefficient and relaxation depth of N 2 O and, as a result, we first report here on these factors for our aerated grassland soil site.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…From the results of the 222 Rn method, average diffusion coefficients and relaxation depths of CO 2 and CH 4 were similar to previous values in aerated sandy soils (Dörr and Münnich 1990;Trumbore, 1990;Dueñas et al 1999;Kim and Tanaka 2002). There are yet few reports for a diffusion coefficient and relaxation depth of N 2 O and, as a result, we first report here on these factors for our aerated grassland soil site.…”
Section: Discussionsupporting
confidence: 49%
“…However, the 222 Rn method does give significant information about trace gas diffusion in the soil throughout the year. Only a small fraction of 222 Rn is produced by recoil from soil particles into the air, depending on the specific surface area of soil particles-and thus depending also on grain size distribution (Trumbore et al 1990;Davidson and Trumbore 1995;Dueñas et al 1999;Kim and Tanaka 2002). 222 Rn flux at the soil surface is affected by 226 Ra contents, as well as soil physical properties such as grain size distribution and resistance to molecular diffusion in the unsaturated soil zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar methodologies were applied to evaluate emissions of CO 2 (Schmidt et al 2003), N 2 O (Schmidt et al 2001), and CFCs (Biraud et al 2000). In another approach, Trumbore et al (1990) estimated the rates of ecosystem gas exchange between the air above and below the soil surface and these between the air inside and above the canopy layer in the Amazon rain forest, using 222 Rn concentration measurements in the soil and the atmosphere. Martens et al (2004) reported on a method for estimating the net ecosystem exchange (NEE) of CO 2 using measurements of atmospheric 222 Rn accumulation in the Brazilian rain forest during night time.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been used to measure trace gas fluxes in grassland (Obrist et al, 2006), forests (Martens et al, 2004;Trumbore et al, 1990;Ussler et al, 1994), and urban areas (Hammer et al, 2009;Lallo et al, 2009;Yver et al, 2009). More generally, this method can be regarded as a specific example of using mixing depth and concentration measurements to infer surface fluxes (Emeis, 2008;Forster et al, 2012).…”
Section: Using Lidar To Improve Radon Measurementsmentioning
confidence: 99%